Injury risk predictors among student badminton players in a Malaysian national sports school: Preliminary study - Goh, S.; Ali, M.; Mokhtar, A.; Mohamed, I. (Elsevier, 2013)
Introduction: Despite being a widely competed sport internationally, badminton injuries is poorly researched. More limited is the work on risk factors for badminton injuries. Hence, this study was done to preliminarily explore possible injury risk predictors among our competitive badminton student athletes.